(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To validate the content, appearance, and semantics of a guide for peristomal skin care in adults with elimination ostomies. Method: A methodological study structured in four phases: 1) Exploratory phase, 2) Development, 3) Validation phase, and 4) Publication. This research presented the validation phase, which includes a) content validation by stomal therapy nurses; b) appearance validation by graphic designers; and c) semantic validation with the target audience (individuals with ostomies and nurses). Data were analyzed using the Content Validation Index (CVI), Appearance Validity Index (AVI), and Semantic Agreement Index (SAI). Results: The final guide comprised 32 pages, divided into pre-textual, textual, and post-textual elements. The global CVI was 88.6%, total AVI was 83.3% and global SAI was 98.2%. Conclusion: The guide was validated as an educational and assistance technology in three stages, presenting clinical applicability in Nursing Consultations, support groups, and self-care for individuals with ostomies and their families. The material has high replicability potential, as it will be available in both digital and print versions.